Leaf orientation of maize plants as influenced by seed positioning in the soil - Matsuo, Osvaldo; Abi Saab, Otávio Jorge Grigoli; Barbosa, André Prechlak; Alves, Luiz Abilio Ribeiro; Zucareli, Claudemir (Semina: Ciências Agrárias, 2020)
Adequate positioning of the seed in the planting furrow allows the maize leaves to be oriented perpendicularly in relation to the sowing row, minimizing overlap and self-shading. The aim of this study was to investigate the positioning of flat and round maize seeds in the furrow and its effects on leaf orientation and plant architecture in the horizontal plane. The experiment was conducted in pots in a greenhouse, using 20C-sieve (flat) and 22R-sieve (round) seeds of the Balu 280 PRO hybrid, at a sowing depth of 0.04 m. The experiment was laid out in a completely randomized design with a 5 Ã— 2 factorial arrangement [five seed positions and two shapes (flat and round)] with eight replicates, totaling 80 plots. Leaf orientation was evaluated at the V3 stage. Seed size and shape did not show a significant interaction with seed positioning, suggesting that maize leaf orientation was only influenced by seed positioning. The treatments involving seeds laid in a vertical position pointing toward the bottom of the pot and horizontally with the face that contains only the endosperm (dorsal face) down are the most favorable, regardless of seed shape.